Open ended problem solving in geometry - Borgersen, Hans Erik (NOMAD Nordic Studies in Mathematics Education, 1994)
This article is a documentation of a project on open ended problem solving in geometry at Agder College. The project is part of a geometry course and is based on co-operation in small groups. Why we did it, how we did it, how it developed, and what came out of it is the main core of the article. Our conclusions are: – It is possible to have students experience the whole process of doing mathematics. – Geometry is a rich resource for finding problems to do so. – It is possible to create learning environments where students co-operate and give each other support to go through the process together. – It is possible to do this within ordinary courses in the first year at college/university. – There has been observable progress on process writing and evaluation. The students' attempt to generalize and formulate new problems are not satisfactory.The emphasis on process writing and evaluation seems to have an effect on the students' motivation and understanding of doing mathematics. – The students experience a great need for encouragement and support in the process of doing mathematics. – Co-operation in small groups is highly recommended by the students.